Expanding the understanding of teacher servant leadership in undergraduates' collaborative learning behavior: A dual-process framework - Hui Weihua (Acta Psychologica)
Using a three-study design, this paper examines the relationship between teacher servant leadership and undergraduates' collaborative learning behavior. We suggest that, on the one hand, teacher servant leadership can positively relate to undergraduates' collaborative learning behavior through increasing their college belongingness. On the other hand, teacher servant leadership can negatively relate to undergraduates' collaborative learning behavior through enhancing their psychological entitlement. The results of Study 1 (an experimental study, N = 50 undergraduates from diverse disciplines), Study 2 (an experimental study, N = 61 science, technology, engineering, and math undergraduates), and Study 3 (a field survey design, N = 209 undergraduates majored in education) consistently revealed that teacher servant leadership indirectly relates to undergraduates' collaborative learning behavior both positively through college belongingness and negatively through psychological entitlement. The findings from the three studies consistently suggest the double-edged nature of a teacher servant leadership in relation to undergraduates' collaborative learning behavior. The importance of these findings for understanding the undergraduates' outcomes of servant leadership is discussed.